A Strategic Framework for Enhancing Brand Value in Intangible Cultural Heritage Tourism: The Case of Liubao Tea in Wuzhou City, China - Guo, Lushan; Kaewnuch, Kanokkarn (Journal of Cultural Analysis and Social Change, 2025)
This study aims to examine the factors influencing the brand value of intangible cultural heritage (ICH) tourism from the visitors’ perspective, using Liubao tea tourism in Wuzhou City, Guangxi Province, China, as a case study. It further seeks to propose strategic guidelines for enhancing brand value in ICH tourism destinations. A mixed-methods research design was employed. The quantitative phase involved a structured questionnaire administered to 400 tourists to assess five core components of brand value: brand awareness, brand image, perceived quality, brand association, and brand loyalty. Statistical analyses included descriptive statistics, t-tests, ANOVA, and multiple regression. The qualitative phase comprised in-depth interviews with 20 stakeholders (tea farmers, tourism providers, government officials), analysed using thematic coding supported by NVivo and triangulation techniques to ensure content validity. The findings indicate that the overall brand value of Liubao tea tourism is rated at a high level by visitors, with brand loyalty emerging as the most influential factor. Destination-related elements—specifically cultural heritage, physical infrastructure, and service quality—significantly affect brand value, while tourist behavioral factors show no statistically significant impact. Government support, especially from central authorities via policies, tax incentives, and transportation development, also positively influences brand perception. Storytelling, environmental aesthetics, and authentic experiences contribute to enhanced brand identity and emotional resonance with visitors. Brand value in ICH tourism can be effectively built by aligning cultural authenticity with strategic branding efforts. Liubao tea tourism demonstrates a successful model for integrating heritage-based storytelling, local engagement, and sustainable tourism practices. These elements enhance visitors’ perceptions and foster loyalty. Despite Liubao’s cultural richness, challenges remain in strengthening brand awareness and emotional association. Fragmented marketing efforts, limited international recognition, and gaps in digital engagement present obstacles to maximizing brand potential. Addressing these complications through targeted branding and cross-sector collaboration is critical for sustaining competitiveness in the growing ICH tourism sector.